Spread of Epidemics and Rumours with Mobile Agents - Draief, M. (Progress in Industrial Mathematics at ECMI 2008, 2010)
We propose a simple model of infection that enables to study the coincidence time of two random walkers on an arbitrary graph. By studying the coincidence time of a susceptible and an infected individual both moving in the graph we obtain estimates of the infection probability. The main result of this paper is to pinpoint the impact of the network topology on the infection probability.